Complexity of Functional Urban Spaces Evolution in Different Aspects: Based on Urban Land Use Conversion. (27th September 2020) - Zhou, Guolei; Li, Chenggu; Liu, Yanjun; Zhang, Jing
Abstract : The evolution of urban spatial structure and urban land use is a topical issue in urban studies. The analysis of the complexity of functional urban spaces evolution is valuable for a deeper understanding of the changes in urban spatial structure. Taking the central city of Changchun as the study area, the paper uses the urban land conversion method to analyze the spatial and temporal characteristics of functional urban spaces evolution in different aspects. The study found that the evolution of functional urban spaces presents significant spatial and temporal differences in different stages and different aspects. There is a close relationship between functional urban spaces evolution and scale. As the scale becomes smaller, the spatial differences and patterns of functional urban spaces evolution become more complex. In the context of rapid urbanization, the mutual replacement of functional urban spaces is frequent, which is not conducive to the sustainable development of urban space as a whole. This study will deepen the understanding of the evolution of urban spatial structure and the complexity of urban systems and provide theoretical support for the optimization and sustainable development of urban spaces.